2015
DOI: 10.1186/s13098-015-0086-4
|View full text |Cite
|
Sign up to set email alerts
|

High glucose induces and activates Toll-like receptor 4 in endothelial cells of diabetic retinopathy

Abstract: BackgroundHyperglycemia-induced inflammation causes the dysfunction of blood vessels, and Toll-like receptor 4 (TLR4) plays a key role in inflammation-induced angiogenesis. However, the impact of TLR4 on the pathogenesis of diabetic retinopathy (DR) is poorly understood. In this study, we examined the expression of TLR4 in retinal vascular endothelial cells of patients with DR and diabetic mice, and explored the role of TLR4 in mediating inflammatory responses by human microvascular endothelial cells (HMEC-1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 36 publications
2
46
0
1
Order By: Relevance
“…Pahwa et al found that TLR4 mediate hyperglycemia induced macrovascular aortic endothelial cell inflammation and perturbation of the endothelial glycocalyx [47]. And high glucose could also induce and activate TLR4 in endothelial cells of diabetic retinopathy [48, 49]. The present study demonstrated that TLR4 knock-down curbed the abnormal proliferation of mesangial cells induced by hyperglycemia, which was in accordance with the others reports.…”
Section: Discussionsupporting
confidence: 91%
“…Pahwa et al found that TLR4 mediate hyperglycemia induced macrovascular aortic endothelial cell inflammation and perturbation of the endothelial glycocalyx [47]. And high glucose could also induce and activate TLR4 in endothelial cells of diabetic retinopathy [48, 49]. The present study demonstrated that TLR4 knock-down curbed the abnormal proliferation of mesangial cells induced by hyperglycemia, which was in accordance with the others reports.…”
Section: Discussionsupporting
confidence: 91%
“…The inflammatory response produces numerous inflammatory mediators to accelerate the apoptosis of endothelial cells, and vascular permeability [5]. The endothelial cell activation in response to inflammatory stimuli is an initial event in diabetic retinopathy [6] and atherosclerosis [7]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition to responding to the foreign pattern recognition molecules, TLR4 binds to a range of endogenous ligands such as high-mobility group chromatin protein B1 (HMGB1) which was reported to play a significant role in many angiogenesis-related conditions (37)(38)(39). TLR4 is highly expressed and activated in hypoxic and ischemic ocular diseases such as ROP and diabetic retinopathy (40,41). TLR4 2/2 mice presented with significantly attenuated NV and avascular areas in the OIR model (25), consistent with the results from the pharmacologic inhibitor TAK-242.…”
Section: Discussionmentioning
confidence: 99%